MUZARA’AH DAN PENGEMBANGAN EKONOMI UMAT DI PEDESAAN - Firman Muh. Arif (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2018)
The concept of muzara'ah is an Islamic intellectual heritage whose practice is still possible to be applied in the reality of people's lives. The application of muzara'ah in the era of modern society is carried out with mechanisms that are relevant to existing developments but still consistent with the basis and values of Islamic ideals. This paper reviews some things that are descriptive and explorative with sociological and welfare approaches. The application of muzara'ah is no longer limited to agriculture and has the opportunity to be developed in various other fields with the basic principle of profit sharing. The application of muzara'ah aims to minimize land that is not empowered, to prosper the marginalized land. absorb labor for those who are competent to manage but do not own land, reduce the gap between the owners of capital and land with cultivators, and boost the productivity of the land. Revitalization of muzara'ah shows that the concept can still exist in the present by modernizing its operational techniques, institutionalizing muzara'ah so that the impact is practical and useful for the public, leaning towards improving conditions and presenting comprehensive Islam.